Cell cycle-dependent regulation of plant infection by the rice blast fungus Magnaporthe oryzae. Issue 5 (2nd November 2017) - Osés-Ruiz, Míriam; Talbot, Nicholas J.
ABSTRACT: The rice blast fungus Magnaporthe oryzae forms a specialized infection structure called appressorium which uses a turgor-driven mechanical process to breach the leaf cuticle and gain entry into plant tissue. Appressorium development and plant infection are regulated by cell cycle progression and critically depend upon two, temporally separated S-phase checkpoints. Following conidial germination on the rice leaf surface, an S-phase checkpoint is essential for appressorium differentiation and operates through the DNA damage response pathway. By contrast, appressorium maturation and penetration peg development require S-progression that depends on turgor control. In this mini-review, we describe cellular mechanisms associated with cell cycle-dependent regulation of appressorium development and the potential operation of morphogenetic checkpoint control of plant infection.